2016
DOI: 10.1007/s13670-016-0184-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Bilateral Upper Extremity Coordination

Abstract: Although evidence exists that changes in sensorimotor function occur with aging, changes in the bilateral coordination of the upper extremities is less understood. Here, we review the behavioral and neural evidence of declines in bilateral coordination as well as the implications these deficits have on function and physical rehabilitation. We begin with an introduction to the two major forms of bilateral coordination, symmetric and non-symmetric and their sub-groupings. After discussing the motor performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
(103 reference statements)
0
15
0
2
Order By: Relevance
“…While the literature on age-related changes in hand function is abundant, less is known about changes in the level of functional asymmetry with advancing age. Reports do indicate that senescence is associated with overall decreased hand coordination [ 20 ] and that changes in sensorimotor performance may significantly reduce quality of life in old age [ 21 , 22 , 23 ]. Nonetheless, the effects of normal aging on inter-hand differences are not fully explained and are worthy of multidisciplinary investigation.…”
Section: Introductionmentioning
confidence: 99%
“…While the literature on age-related changes in hand function is abundant, less is known about changes in the level of functional asymmetry with advancing age. Reports do indicate that senescence is associated with overall decreased hand coordination [ 20 ] and that changes in sensorimotor performance may significantly reduce quality of life in old age [ 21 , 22 , 23 ]. Nonetheless, the effects of normal aging on inter-hand differences are not fully explained and are worthy of multidisciplinary investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Potential neurophysiological mechanisms underlying impaired interlimb coordination in older adults include altered functions in (a) the corpus callosum and (b) the cerebellum. During bilateral movement tasks, we must address interhemispheric connections through balancing interhemispheric inhibitions between hemispheres for successful task completion [35]. Brain imaging studies reported that older adults exhibited a smaller volume of the corpus callosum and reduced white matter integrity than young adults [36].…”
Section: Discussionmentioning
confidence: 99%
“…Capacities such as joint mobility, strength and motor coordination are required to perform basic daily activities [38]. For the purpose of this review, upper limb functions were separated into two categories:…”
Section: Descriptions Of Upper Limb Functionsmentioning
confidence: 99%